MASALAH-MASALAH YAN G DIHADAPI SISWA DALAM PEMBELAJARAN SEJARAH KELAS XI IPS Dl SlIA SEMEN PADANG - NINGSIH, SURYA FATMI ADE (Pendidikan Sejarah, 2014)
This research results  in the wake of the  low student studying  history   in social studies class XI   at   Semen Padang   senior high school. Thi s study aims to  I) describe the problems  faced by students in learning the history of class XI social 2 and X I social 3 semester January-Jun e period  of the academic  year 2013/2014  at  SMA  Semen  Padang  and , 2)  descnbe  the  factors  that influence  the effect of the problems of students in  learning  the history of class Xl  social  2  and XI social  3 semester  January-June  period  of  the academic  year  2013/2014  at  SMA  Semen  Padang . The method used in this research is descriptive qualitative. The results of tbis research showed about the problems faced by students in learning history consists of, the internal and external problems .  Internal   problems  experienced  by  students  in  learning  history  consists  of,   ( I)  many student that low interested to learning hi story. Caused by the intelligence factor and factor methods. (2) poor to attention or follow the learning activity. Caused by an interest fac1or and factor methods. (3) poor concentration i n learning. Caused by a factor of motivation and school time. (4) did not repeated the lesson at home. Caused by friends. Moreover, external factors consist of,(I) the effect of the socia l environment. Caused  by a student  friend , at home and school.(2) l ess faci litate and infrastructure  that use in  learning history because most of teacher onl y use one reference in teaching learning process. Thi s problems caused due to lack of use media in learning.